Climate Change and the Ecological Analysis of Law. The Contribution of the Comparative Lawyer to the Climate Emergency (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In the search for new approaches for the study of law attuned to nature, some recent proposals aimed at switching from the «economic» to the «ecological» analysis of law appear to be of interest. While the climate and environmental crisis was initially explored by public lawyers, for some time now ecological goals have also begun to penetrate private law. In particular, an attempt will be made to ascertain whether the contract in its new «sustainable» form can be an appropriate instrument for reversing the course or whether a «sustainability with the State» is to be preferred.
Keywords: Climate change; ecological analysis of law; sustainable development; corporate social responsibility; sustainable contracts